Air France internet marketing : optimizing Google, Yahoo!, MSN, and Kayak sponsored search - Jeffery, Mark ([London] : SAGE, 2016)
Rob Griffin, senior vice president and U.S. director of search for Media Contacts, a communications consulting firm, is faced with the task of optimizing search engine marketing (SEM) for Air France. At the time of the case, SEM had become an advertising phenomenon, with North American advertisers spending $9.4 billion in the SEM channel, up 62% from 2005. Moving forward, Griffin wants to ensure that the team keeps its leading edge and delivers the results Air France requires for optimal Internet sales growth. This case study examines his efforts.
Originally Published in: Jeffrey, M., Egli, L., Gieraltowski, A., Lambert, J., Miller, J., Neely, L., Sharma, R. (2009). Air France Internet marketing: optimizing Google, Yahoo!, MSN, and Kayak sponsored search. (Teaching note revised 02/03/2015). 5-407-753. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Air France; Airlines -- Marketing -- Case studies; Internet marketing -- Case studies